Socio-Economic and Administrative-Territorial Changes on the Eve of the Zoning of Samarkand (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article analyzes the socio-economic, political and administrative conditions of the Samarkand region, one of such areas, on the eve and during the period of regionalization. The article briefly mentions that the Samarkand region is a political, economic, administrative and cultural center, occupying an important position not only in Uzbekistan, but also in Central Asia.